Laser‐Triggered Small Interfering RNA Releasing Gold Nanoshells against Heat Shock Protein for Sensitized Photothermal Therapy. Issue 2 (19th October 2016) - Wang, Zhaohui; Li, Siwen; Zhang, Min; Ma, Yi; Liu, Yuxi; Gao, Weidong; Zhang, Jiaqi; Gu, Yueqing
Abstract : The resistance of cancer cells to photothermal therapy is closely related to the overexpression of heat shock proteins (HSPs), which are abnormally upregulated when cells are under lethal stresses. Common strategies that use small molecule inhibitors against HSPs to enhance hyperthermia effect lack spatial and temporal control of drug release, leading to unavoidable systemic toxicity. Herein, a versatile photothermal platform is developed which is composed of a hollow gold nanoshell core densely packed with small interfering RNAs against heat shock protein 70 (Hsp70). Upon near infrared light irradiation, the small interfering RNAs can detach from gold surface specifically and escape from endosomes for Hsp70 silencing. Meanwhile, the temperature increases for hyperthermia therapy due to the high photothermal efficiency of the nanoshells. Efficient downregulation of Hsp70 after light activation is achieved in vitro and in vivo. Ultimately, the light‐controlled dual functional nanosystem, with the effects of Hsp70 silencing and temperature elevation, results in sensitized photothermal therapy in nude mice model under mild temperature. This strategy smartly combines the localized photothermal therapy with controlled Hsp70 silencing, and has great potential for clinical translation with a simple and easily controlled structure. Abstract : A versatile and unique photothermal platform based on gold nanoshells is developed to overcome the thermal resistance of cancer cells. The dual functional near infrared light specifically releases small interfering RNAs from gold surface for silencing heat shock protein, and increases temperature to synergize with the gene silencing effect for sensitized hyperthermia therapy.